STRATEGI CAPACITY BUILDING APARATUR PEMERINTAH DESA DALAM PENGEMBANGAN DESA WISATA GARUDA BERBASIS MASYARAKAT LOKAL (STUDI DI DESA KEDISAN, KECAMATAN TEGALLALANG, KABUPATEN GIANYAR) - Cahyaniti, I Gusti Ayu Rima; Wismayanti, Kadek Wiwin Dwi; Wijaya, Komang Adi Sastra (CITIZEN CHARTER, 2022)
Kedisan Village is designated as a tourist village based on Gianyar Regent Regulation No. 429/E02/2017 concerning Determination of Tourism Villages in Gianyar Regency. Various efforts have been made by the Kedisan Village government in the context of developing a tourist village. Over time, development efforts have decreased tourist visits caused by internal and external factors. This research uses a qualitative descriptive research type. The analysis used is the indicator of strategic management by Wheelen and Hunger and the concept of capacity building according to Grindle. The results showed that the tourism village development activities have been running quite well but not yet fully running optimally. There are still several obstacles, namely in determining strategy and policy directions, low coordination between parties, the Covid-19 pandemic, as well as the low quality of human resources in the tourism sector and the lack of public awareness in seeing the opportunities that exist. Keywords: Tourism Village, Strategic Management, Capacity Building, SWOT Analysis